2019
DOI: 10.5104/jiepeng.12.e19-003-1
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Radiolysis-based Three Dimensional Additive Manufacturing Process

Abstract: To achieve the three dimensional additive manufacturing process, we investigated X-ray radiolysis-induced photochemical reaction of Cu(CH 3 COO) 2 solution. Here, we demonstrated synthesis and immobilization of copper and copper oxide particles onto an aluminium substrate directly from the liquid solution. The particles are formed in the X-ray radiolysis of flowing aqueous solutions of Cu(CH 3 COO) 2 which also contain methanol as ⋅ OH scavenger. We found that the sizes and compositions of the particles depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…They also reported that the synthesized candy-like Cu 4 O 3 microstructure exhibits good long-term antibacterial activities to both E. coli and S. aureus bacteria because the release of Cu 2+ ions from the Cu 4 O 3 is responsible for the antibacterial activity. On the other hand, Yamaguchi et al have added the X-ray-radiolysisinduced photochemical synthesis of copper oxide materials as liquid-based phase reaction (Yamaguchi et al, 2016a(Yamaguchi et al, ,b, 2017(Yamaguchi et al, , 2019Saegusa et al, 2019). Until now, a single Cu 4 O 3 phase has not been obtained by X-ray-irradiation of the liquid phase.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…They also reported that the synthesized candy-like Cu 4 O 3 microstructure exhibits good long-term antibacterial activities to both E. coli and S. aureus bacteria because the release of Cu 2+ ions from the Cu 4 O 3 is responsible for the antibacterial activity. On the other hand, Yamaguchi et al have added the X-ray-radiolysisinduced photochemical synthesis of copper oxide materials as liquid-based phase reaction (Yamaguchi et al, 2016a(Yamaguchi et al, ,b, 2017(Yamaguchi et al, , 2019Saegusa et al, 2019). Until now, a single Cu 4 O 3 phase has not been obtained by X-ray-irradiation of the liquid phase.…”
Section: Resultsmentioning
confidence: 99%
“…We performed synchrotron-radiation-induced X-ray radiolysis experiments using beamline BL8S2 at the Aichi Synchrotron Radiation Center, Aichi Science and Technology Foundation (Yamaguchi et al, 2015(Yamaguchi et al, , 2016a(Yamaguchi et al, ,b, 2017(Yamaguchi et al, , 2019Saegusa et al, 2019). The storage ring current and energy were in operation at 300 mA and 1.2 GeV with super-bending magnets of 5 T. The X-ray spectrum is displayed in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations